Circulating Rheumatoid and Antinuclear Factors in Asbestos Workers - Turner-Warwick, Margaret (1970)
In an unselected series of 80 patients with asbestos exposure referred to the London Pneumoconiosis Medical Panel, antinuclear and rheumatoid factors were found in 28 and 27% respectively. This probably represents at least a fourfold increase over their incidence in random populations. The presence of these autoantibodies was not related to the duration of exposure, but was related to the extent of radiographic abnormality.